2020
DOI: 10.1016/j.psj.2019.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Short cold exposures during incubation and postnatal cold temperature affect performance, breast meat quality, and welfare parameters in broiler chickens

Abstract: Cold stimulations during egg incubation were reported to limit the occurrence of ascites in broilers subjected to cold temperature after 14 d of age. However, data are lacking on the impacts of such strategy in case of cold temperature conditions at start. This study aimed to evaluate the effects of incubation and posthatch cold challenge on performance, breast muscle integrity, and meat processing quality in broiler chickens. Ross 308 eggs were incubated under control temperature (I 0 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 64 publications
0
23
0
1
Order By: Relevance
“…2 0.5 ± 0.08 ns 14 days-old NA (pg/µg) ♀ 11.4 ± 2.6 8.5 ± 1.0 8.9 ± 1.4 ns ♂ 7.5 ± 0.9 6.7 ± 0.9 7.8 ± 0.8 ns compensate their growth later on after periods of growth delay caused by cold (Mortola, 2009). Likewise, Nyuiadzi et al (2020) observed that males exposed to a lower incubation temperature presented a higher body mass under cold exposure during rearing, while females incubated in a cold temperature have greater growth at normal post-hatching temperatures. These effects of cold incubation on BM are possibly a result of hormonal differences between sexes in the very early embryo development and in the early growth phases (Dainat et al, 1991;Kocamis et al, 1998;Bello et al, 2014;Nyuiadzi et al, 2020).…”
Section: Ltmentioning
confidence: 99%
“…2 0.5 ± 0.08 ns 14 days-old NA (pg/µg) ♀ 11.4 ± 2.6 8.5 ± 1.0 8.9 ± 1.4 ns ♂ 7.5 ± 0.9 6.7 ± 0.9 7.8 ± 0.8 ns compensate their growth later on after periods of growth delay caused by cold (Mortola, 2009). Likewise, Nyuiadzi et al (2020) observed that males exposed to a lower incubation temperature presented a higher body mass under cold exposure during rearing, while females incubated in a cold temperature have greater growth at normal post-hatching temperatures. These effects of cold incubation on BM are possibly a result of hormonal differences between sexes in the very early embryo development and in the early growth phases (Dainat et al, 1991;Kocamis et al, 1998;Bello et al, 2014;Nyuiadzi et al, 2020).…”
Section: Ltmentioning
confidence: 99%
“…Several attempts have been made to improve the thermo-tolerance of chickens to adapt to heat stress conditions such as heat acclimation, including the use of thermal conditioning ( Yahav and Hurwitz 1996 ; Yahav and Plavnik, 1999 ; Willemsen et al., 2010 ; Nyuiadzi et al., 2020 ). During the last few days of incubation, chicken embryos grow faster, and their rate of nutrient utilization increases ( Elwan et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Nyuiadzi et al (2020) reported slightly less white striping occurrence at D40, when Ross 308 chicken embryos from 36-wk-old breeders, incubated at constant 37.6 • C (99.68 • F) and 70% RH were exposed to 15 • C and 81% RH for 30 minutes at days 18 and 19. This treatment also had improvements in final body weight (37 grams) compared to the control, but no effects on feed efficiency, carcass and cut up part yields, or meat quality.…”
Section: Evidence Of Incubation Effects On Muscle Development and Myomentioning
confidence: 99%
“…The environmental conditions post-hatch may affect the responses of hatchlings to incubation treatments. The treatment reported by Nyuiadzi et al (2020) was a short cold exposure that could occur when transferring eggs from setters to hatchers. As far as brooding conditions are adequate, it seems reducing embryo metabolic heat during this period (ED18 and ED19) is positive to reduce white striping.…”
Section: Evidence Of Incubation Effects On Muscle Development and Myomentioning
confidence: 99%
See 1 more Smart Citation